2020
DOI: 10.1007/s40123-020-00262-w
|View full text |Cite
|
Sign up to set email alerts
|

Video Conferencing in the Intravitreal Injection Clinic in Response to the COVID-19 Pandemic

Abstract: Purpose: To share a useful intervention to minimize risk of COVID-19 infection to both healthcare workers and patients in the eye clinic. Methods: We present our experience of virtual, within-clinic remote visual acuity assessment to reduce the risk of infection with COVID-19. Results: Along with standard recommendations for personal protective equipment and hand hygiene to contain viral spread and treating only urgent cases, remote within-clinic visual acuity testing and consultations can be undertaken with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A 2020 systematic review found that virtual clinics improved the provision of healthcare and reduced the transmission of the virus during the outbreak [10]. Studies found a mixed patient response to pandemic telehealth measures [11][12][13] but found robust evidence concerning safety in light of the pandemic [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 systematic review found that virtual clinics improved the provision of healthcare and reduced the transmission of the virus during the outbreak [10]. Studies found a mixed patient response to pandemic telehealth measures [11][12][13] but found robust evidence concerning safety in light of the pandemic [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was carried out in 2019, telemedicine programs in ophthalmology have further developed and become increasingly utilized globally during the COVID-19 pandemic of 2020. [16][17][18] Eye care centers have made efforts to reduce unnecessary eye care visits to enable adherence to social distancing guidelines, particularly for elderly and highrisk patients in clinic. 19 Given the advantages of telemedicine, remote eye care delivery will likely continue to some degree even after the COVID-19 pandemic ends.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, based on a preliminary literature review (search terms and results described in online supplemental appendix A ), since the start of the COVID-19 pandemic, only a handful of countries (eg, USA, UK, India, Hong Kong, Singapore) 14–18 had reported adoption of teleconsultations in ophthalmology thus far. These currently reported adoptions were mainly limited to subspecialties of medical retina, 17 neuro-ophthalmology 19 20 and paediatric ophthalmology. 21 This further highlights the need to fuel wider implementation of telemedicine and digital health models for ophthalmology in the current climate of COVID-19.…”
Section: Principle Considerations In the Post-covid-19 Pandemic ‘New ...mentioning
confidence: 99%